Workplace health and safety and the future of work: Evidence from linked-unit record data - Juliane Hennecke; Lisa Meehan; Gail Pacheco (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2023)
Despite presenting potentially significant challenges and opportunities, the possible implications for workplace health and safety (WHS) of future-of-work trends have so far received scant attention. This paper, therefore, empirically examines the relationship between future-of-work trends and workplace injuries. It undertakes multivariate regression analysis using population-level accident compensation data for New Zealand linked to other data sources within Stats NZ's Integrated Data Infrastructure (IDI) and Longitudinal Business Database (LBD), including information on business practices related to the future-of-work. It finds that work-related injury claim rates tend to increase with age, which presents a potential challenge for WHS given the ageing workforce. The injury claim rate decreases as job tenure increases, suggesting that future-of-work trends that increase the rate of job switching, such as nonstandard work and technological change, also present a challenge. Workers in industries such as agriculture and manufacturing have relatively high injury claim rates, suggesting that the ongoing shift away from these higher-risk industries and towards lower-risk service industries is positive for WHS outcomes. In addition, the finding that workers in firms with high levels of automation have lower injury claim rates highlights the potential of automation to remove workers from potentially hazardous situations. While workers in firms that offer flexible working arrangements, such as working from home, have lower injury claim rates, this is likely to be largely due to the nature of the jobs that are amenable to flexible work arrangements.
Keywords: 330; workplace health and safety; work-related injury; future of work